Bureaucracy, underground activities, and fluctuations - Gerasimos T. Soldatos (Atlantic Review of Economics, 2014)
This is a note on corruption and underground economy in a Kaldor-type model of the business cycle. It appears that when the economy is booming and underground activities seek to enter the official economy, bureaucrats have the upper hand but until underground businesses cannot tolerate bureaucrats anymore and start reentering the informal sector. This is what checks the growth of the official output and gets it into its downward phase. Once in this phase, bureaucrats lose control and just follow passively the developments in the economy. At the trough of the contraction, official activities reach their nadir whereas the unofficial ones are at their zenith and seek to buy whatever has been left from the staggering official businesses. This is what leads to recovery in the absence of stabilization policies.
Keywords: D73; E32; O17; 330; Bureaucracy; Corruption; Underground Economy; Business Cycle